Temperature evolution of the effective magnetic anisotropy in the MnCr2O4 spinel - Tobia, Dina (2015)
In this work, we present a study of the low temperature magnetic phases of polycrystalline MnCr2O4 spinel through dc magnetization and ferromagnetic resonance spectroscopy (FMR). Through these experiments, we determined the main characteristic temperatures: TC ∼ 41K and TH ∼ 18K corresponding, respectively, to the ferrimagnetic order and to the low temperature helicoidal transitions. The temperature evolution of the system is described by a phenomenological approach that considers the different terms that contribute to the free energy density. Below the Curie temperature, the FMR spectra were modeled by a cubic magnetocrystalline anisotropy to the second order, with K1 and K2 anisotropy constants that define the easy magnetization axis along the 〈110〉 direction. At lower temperatures, the formation of a helicoidal phase was considered by including uniaxial anisotropy axis along the [110] propagation direction of the spiral arrange, with a Ku anisotropy constant. The values obtained from the fittings at 5K are K1 = -2.3 × 104 erg cm-3, K2 = 6.4 × 104 erg cm-3 and Ku = 7.5 × 104 erg cm-3.